Macro-Prudential policy instruments, pro-cyclicality of capital and bank lending in Nigeria: From post-global financial crisis - Onyebuchi Iwegbu; Ernest S.O. Odior (Jos Journal of Economics, 2019)
This study empirically examined the tendency of macro-prudential policy in reducing the pro-cyclicality between Nigeria banks' capital and bank loans during the post global financial crisis. The study employed the ARDL Model in estimating the model specified. The study found that macro-prudential policies help in reducing the procyclicality between bank loans and the extent of capital available for banks. And this is found to be less effective during the crisis than when the financial industry is not in crisis. Also, in the short run, capital and bank loans are countercyclical in nature and however this is reversed in the long run. The policy implication of this study is that the regulatory authority's macro-prudential policy is effective in reducing the procyclicality between banks loans and capital adequacy of banks. Also, short term crisis does not deter banks from issuing out loans, however, in the long run, loans are greatly affected by the crisis within the system. There is a need for policymakers and the regulatory authority to focus attention on regulatory capital framework so that macro-prudential policies will have a greater impact in reducing the credit growth procyclicality and strengthen their macroprudential supervision measures especially during the period of crisis.
Keywords: E58; G28; 330; Macro-prudential Policy Instruments; Bank's Capital; Bank Loans; ARDL